Risk factors for metabolic syndrome in young school adults (Research, Society and Development, 2020)
Objetive: To analyze the association of diagnostic criteria for Metabolic Syndrome with sociodemographic and clinical characteristics in young schoolchildren. Methods: Analytical study conducted with 320 young adult schoolchildren from Fortaleza-Ceará-Brazil. Results: It was shown that the frequency of cases of one, two and three altered criteria for Metabolic Syndrome was 254, 58 and eight, respectively. Overweight affected 56.6% of young adult schoolchildren surveyed. In the final regression model, the markers remained: exposure to alcohol, history of high cholesterol in the family and Body Mass Index in students with one of the criteria changed to Metabolic Syndrome and exposure to alcohol and history of high cholesterol in the family in students with two criteria for Metabolic Syndrome changed. Conclusion: It is concluded that exposure to alcohol, a history of high cholesterol in the family and the Body Mass Index were associated with the presence of one or two altered criteria for the diagnosis of Metabolic Syndrome, thus showing the multifactoriality involved in this issue.